(untitled) (Communications in Mathematical Research, 2019)
We mainly study the periodicity theorems of meromorphic functions having truncated or partial sharing values with their shifts, where meromorphic functions are of hyper order less than 1 and N(r, f)=α T(r, f) for some positive number α.